2023
DOI: 10.3390/ani13061032
|View full text |Cite
|
Sign up to set email alerts
|

Ante-mortem and Post-mortem Inspection and Relationship between Findings in a North Albanian Pig Slaughterhouse

Abstract: In June 2014, Albania was granted EU candidate status, thus starting a process of compliance with the membership criteria. In this context, a modern meat inspection approach in line with the European legislation was applied to a pig slaughterhouse in northern Albania in order to investigate the ante-mortem (AM) and post-mortem (PM) conditions and the relationship between these findings. For this purpose, 3930 pigs divided into 35 batches were evaluated over a 3-month period. The most frequent AM conditions rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Respiratory diseases have a great impact on animal health and welfare, causing substantial economic losses in intensive pig production (Meyns et al, 2011;Andoni et al, 2023;Petri et al, 2023). Surveillance and evaluation of risk factors are important means of monitoring and controlling these kinds of diseases and the slaughterhouse is a strategic point for data collection for this purpose (Merialdi et al, 2012;Correia-Gomes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory diseases have a great impact on animal health and welfare, causing substantial economic losses in intensive pig production (Meyns et al, 2011;Andoni et al, 2023;Petri et al, 2023). Surveillance and evaluation of risk factors are important means of monitoring and controlling these kinds of diseases and the slaughterhouse is a strategic point for data collection for this purpose (Merialdi et al, 2012;Correia-Gomes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bottacini et al (2021) found that there is a positive correlation between fibrinous pericarditis and severe pleuritis. Liver milk spots, that usually occur asymptomatically, may be associated with the increase the prevalence of EP-like lesions (Correia-Gomes et al, 2017; Andoni et al, 2023).…”
Section: Introductionmentioning
confidence: 99%